Alexithymia and Facial Mimicry in Response to Infant and Adult Affect-Expressive Faces - Nordmann, Marc A.; Schäfer, Ralf; Müller, Tobias; Franz, Matthias (Frontiers in Psychology, 2021)
Facial mimicry is the automatic tendency to imitate facial expressions of emotions. Alexithymia is associated with a reduced facial mimicry to affect expressions of adults. There is evidence that the baby schema may influence this process. In this study it was tested experimentally whether facial mimicry of the high alexithymic group (AG) is different from the low alexithymic group (CG) in response to dynamic facial affect expressions of children and adults. A multi-method approach (20-point Toronto Alexithymia Scale and Toronto Structured Interview for Alexithymia) was used for assessing levels of alexithymia. From initially 3503 data sets two groups of 38 high and low alexithymic group without relevant mental or physical diseases were matched regarding age, gender, and education. Facial mimicry was induced by presentation of naturalistic affect-expressive video sequences (fear, sadness, disgust, anger, and joy) taken from validated sets of faces from adults (Averaged Karolinska Directed Emotional Faces; AKDF) and children (Picture-Set of Young Children’s Affective Facial Expressions; PSYCAFE). The videos started with a neutral face and reached maximum affect expression within 2 seconds. The response of the groups were measured by facial electromyographic activity (fEMG) of corrugator supercilii and zygomaticus major muscles. Differences in fEMG response (4000 ms) were tested in a variance analytical model. There was one significant main effect for the factor emotion and four interaction effects for the factors group x age, muscle x age, muscle x emotion, and for the triple interaction muscle x age x emotion. The participants of AG showed a decreased fEMG activity in response to the presented faces of adults compared to the CG but not for the faces of children. The affect-expressive faces of children induced enhanced zygomatic and reduced corrugator muscle activity in both groups. Despite existing deficits in the facial mimicry of alexithymic persons, affect-expressive faces of children seem to trigger a stronger positive emotional involvement even in the alexithymic group.